Surface epithelial tumors of ovary - an analysis in a tertiary referral hospital - Ghartimagar, D; Ghosh, A; KC, G; Ranabhat, S; Talwar, OP (Journal of Pathology of Nepal, 2013)
Background: Ovarian cancer accounts for 3% of all cancers in females. About 80% of these are benign, and they occur mostly in young women between 20 and 45 years. Borderline tumors occur at slightly older ages while incidence of malignant tumors increases with age, occurring predominantly in perimenopausal and postmenopausal women. About 190,000 new cases and 114,000 deaths from ovarian cancer are estimated to occur annually worldwide. The aim of the study was to fi nd the incidence of surface ovarian tumor in a tertiary referral centre. Materials and methods: This was a retrospective study carried out in the department of pathology, Manipal Teaching Hospital from January 2001 to December 2012. Specimens were received from the same and other hospitals. Records were retrieved from the departmental data bank and were analyzed. Results: : A total of 310 cases of ovarian tumors have been reported in the same period. Among them, 180 cases were of surface epithelial origin and out of which 24 cases had bilateral tumors. Benign tumors comprised of 148 cases, 6 were borderline and 44 were malignant. Among these, the commonest was serous cystadenoma (98 cases) and the least common was malignant Brenner (2 cases). Combined or mixed tumor was seen in 9 cases. Conclusion: : In our study surface epithelial tumors comprised 58% of all ovarian tumors. In both benign and malignant cases, serous tumor was the commonest followed by mucinous tumors. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 397-402 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7868